The type II secretion system (Xcp) of Pseudomonas putida is active and involved in the secretion of phosphatases. (26th March 2013) - Putker, Florian; Tommassen‐van Boxtel, Ria; Stork, Michiel; Rodríguez‐Herva, José J.; Koster, Margot; Tommassen, Jan
Summary The genome of the Gram‐negative bacterium Pseudomonas putida harbours a complete set of xcp genes for a type II protein secretion system (T2SS). This study shows that expression of these genes is induced under inorganic phosphate (Pi) limitation and that the system enables the utilization of various organic phosphate sources. A phosphatase of the PhoX family, previously designated UxpB, was identified, which was produced under low Pi conditions and transported across the cell envelope in an Xcp‐dependent manner demonstrating that the xcp genes encode an active T2SS. The signal sequence of UxpB contains a twin‐arginine translocation (Tat) motif as well as a lipobox, and both processing by leader peptidase II and Tat dependency were experimentally confirmed. Two different tat gene clusters were detected in the P. putida genome, of which one, named tat‐1, is located adjacent to the uxpB and xcp genes. Both Tat systems appeared to be capable of transporting the UxpB protein. However, expression of the tat‐1 genes was strongly induced by low Pi levels, indicating a function of this system in survival during Pi starvation.